PERAN SERTA MASYARAKAT SEKOLAH DALAM PELAKSANAAN PROGAM USAHA KESEHATAN SEKOLAH DI SMP NEGERI 1 MANADO - Sitepu, Hendra; Ratag, Gustaaf A. E.; Siagian, Iyone T. (Universitas Sam Ratulangi, 2015)
Abstract: One of the strategic efforts to improve the quality of Indonesian human is education and health efforts, so that these efforts can best be done through educational institutions. School as a venue for the teaching and learning process should be